Is there a Lower Bound to the Firm Size Distribution Comparing Transition Economies with an Established Market Economy - John Hutchinson (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
We apply Suttons (1998) framework to compare the firm size distribution of two transition economies, Slovenia and Bulgaria with that of a market economy, Belgium. We find that there exists a minimum degree of inequality in the size of firms. In addition firm size inequality levels in Belgium and Slovenia are found to have comparable values while levels in Bulgaria remain considerably lower. Furthfirmore, we find that the industrial structure in a leading accession country is closest to the structure that we find in a market economy.
Keywords: L11; P2; L6; 330; firm size distribution; transition economies; manufacturing; Betriebsgrößenstruktur; Übergangswirtschaft; Marktwirtschaft; Vergleich; Belgien; Bulgarien; Slowenien